ANALISIS DISTRIBUSI FRAGMENTASI BATUAN HASIL PELEDAKAN MENGGUNAKAN SOFTWARE SPLIT DEKSTOP V2.0 DI PT AMMAN MINERAL NUSA TENGGARA - Ade Kurniawan; Alpiana Alpiana; Diah Rahmawati (Universitas Muhammadiyah Mataram, 2020)
PT Amman Mineral Nusa Tenggara merupakan perusahaan tambang yang berlokasi di Batu Hijau Kecamatan Maluk Kabupaten Sumbawa Barat Provinsi Nusa Tenggara Barat. Sebelum dilakukan peledakan terlebih dahulu dilakukan pengeboran untuk menyediakan lubang. BOCCOST (Blasting Optimation Crushing Conveying Optimizing SAG Troughput) program bertujuan untuk menganalisis distribusi ukuran fragmentasi hasil peledakan yang berkaitan dengan pengeluaran SAG Mill dengan menggunakan media software yang disebut Split Enggineering atau Split Dekstop V2.0. Adapun tahapan analisis fragmentasi yaitu menyiapkan gambar untuk diproses, automatic Delination of the Particles, edit Binary Image, computer Size dan graphs and Outputs. Setelah gambar diolah dalam software, maka akan didapatkan ukuran P20. P50, P80 dan Top Size. Selanjutnya akan dimasukkan ke dalam tabel data agmentasi batuan hasil kegiatan peledakan. Hasil analisis fragmentasi pada level 225, 315 dan 345 diperoleh nilai P20 (Limiting Reduction Ratio) dengan ukuran antara 13,74 mm hingga 28,61 mm, P50 (Aperent Reduction Ratio) dengan ukuran antara 38,46 mm hingga 100,06 mm, P80 (Reduction Ratio 80) dengan ukuran antara 68,19 mm hingga 121,70 mm dan Top Size (Working Reduction Ratio) dengan ukuran antara 156,77 mm hingga 322,06 mm. ABSTRACT PT Amman Mineral Nusa Tenggara is a mining company located in Batu Hijau, Maluk District,West Sumbawa Regency, West Nusa Tenggara Province. Before blasting, drilling is carried out to provide holes.The BOCCOST (Blasting Optimization Crushing Conveying Optimizing SAG Troughput) program aims to analyze the size distribution of blasting results related toSAG Mill release using a media software called Split Enggineering or Split Desktop V2.0. The fragmentation analysis stages are preparing images for processing, automatic Delination of the Particles, editing Binary Images, computer Size and graphs and Outputs.The results of fragmentation analysis at levels 225, 315 and 345 obtained P20 (Limiting Reduction Ratio) values with sizes ranging from 13.74 mm to 28.61 mm, P50 (AperentReduction Ratio) with sizes ranging from 38.46 mm to 100.06 mm, P80 (Reduction Ratio 80) with sizes ranging from 68.19 mm to 121 .70 mm and Top Size (Working Reduction Ratio) with sizes ranging from 156.77 mm to 322.06 mm. ABSTRACT PT Amman Mineral Nusa Tenggara is a mining company located in Batu Hijau, Maluk District, West Sumbawa Regency, West Nusa Tenggara Province. Before blasting, drilling is carried out to provide holes.The BOCCOST (Blasting Optimization Crushing Conveying Optimizing SAG Troughput) program aims to analyze the size distribution of blasting results related to SAG Mill release using a media software called Split Enggineering or Split Desktop V2.0. The fragmentation analysis stages are preparing images for processing, automatic Delination of the Particles, editing Binary Images, computer Size and graphs and OutputsThe results of fragmentation analysis at levels 225, 315 and 345 obtained P20 (Limiting Reduction Ratio) values with sizes ranging from 13.74 mm to 28.61 mm, P50 (Aperent Reduction Ratio) with sizes ranging from 38.46 mm to 100.06 mm, P80 (Reduction Ratio 80) with sizes ranging from 68.19 mm to 121 .70 mm and Top Size (Working Reduction Ratio) with sizes ranging from 156.77 mm to 322.06 mm.